Education as a Community Activity: University for Man - Joseph K. Rippetoe; Sue C. Maes (Educational Considerations, 1974)
University for Man is a 7-year-old free university program in Manhattan, Kansas, offering approximately 200 classes each semester. UFM is a community-wide experiment in leisure-time "therapy" involving more than 7,000 participants a year, 50 per cent of whom are non-university students.